Makiusap sa Diyos - Brocka, Lino
Dolores, a kindhearted novitiate devoted to her faith, sees her life take a turn for the worse after becoming the victim of rape. And instead of gaining sympathy, she punished by her superiors to something she did not will, prompting her to flee the nunnery.